Tribal proclivity and its effects on the cooperate existence of Nigeria in the centenary era: an Islamic perspective - Muhammad, Usman Jimoh (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
The paper consists of seven sub-sections namely, the introduction, a flash on the prevalence of tribal proclivity in Nigeria, causes of tribal proclivity among Nigerians and its effects. Other aspect of the paper includes the Islamic perspective on tribal proclivity in Nigeria, recommendations and conclusion. The introduction briefly appraises the historical composition of Nigeria in the early nineteen century and its amalgamation in the year 1914. Reference is being made in the paper to cases of tribal proclivity in Nigeria while the causes of tribal penchant include unemployment, selfishness of some politicians, lack of patience and endurance by citizens in their relationship among themselves. Tribal proclivity the paper affirms results into insecurity of lives and properties, portrays evidence of lack of unity and bad governance. The paper examines some relevant verses and prophetic traditions in a bid to redress the situation and recommends that the government and the well to problem of unemployment in the nation. In addition, religious do people in the society should join hands together towards addressing the scholars and other orientation bodies must reorient people towards peaceful coexistence among themselves.